Firearms in Latin America: A Society without Conflict, but without Peace - Álvarez, Carla-Morena (FLACSO - Sede Ecuador, 2022)
This article aims to describe the transfers of small arms and light weapons to Latin America during and after the Cold War, to identify the main changes that occurred with the end of bipolarity and to establish its relationship with the armed violence that the region is experiencing. A review and analysis of reports and data bases, produced by authors and organizations specialized in firearms and conventional weaponry, from the middle of the 20th century to the present is carried out. It is argued that despite their theoretical marginality, during the Cold War, firearms transfers were an important instrument of relations between the powers in conflict and their areas of influence. When the ideological confrontation came to an end, the transfers abandoned geopolitical motivations and began to work within the logic of the market, which has had important implications for armed violence and criminality in Latin America.